The effect of ketapang leaf extract (Terminalia catappa L.) on the number and type of leukocytes in broiler chickens - Mirino, Mario Navyseal; Maslachah, Lilik; Widya Paramita Lokapirnasari; Rachmawati, Kadek; Tacharina, Martia Rani; Hidayatik, Nanik (Jurnal Agro Veteriner, 2025)
Broiler are popular meat-producing birds in Indonesia because they contain high levels of animal protein. Apart from being used in the treatment of infectious diseases, antibiotics are also used as antibiotic growth promoters (AGP). However, the use of antibiotics as feed additives has been prohibited, a natural substitute for AGP is katapang leaves (Terminalia catappa L.). This study aims to determine the effect of administering katapang leaf extract (Terminalia catappa L.) on the number and type of leukocytes in broiler. This study used 24 Cobb strain broiler which were divided into four treatment groups, each group consisting of six replications. The treatment groups were P0 = only given 1% CMC-Na solution, P1 = Katapang leaf extract solution with 5% concentration, P2 = Ketapang leaf extract solution with 10% concentration, P3 = Katapang leaf extract solution with 15% concentration. The treatment is given orally with a syringe, given to chickens aged 21–35 days. At the end of the study, 2 ml–3 ml of blood is taken from the brachial vein. Data were analyzed using Analysis of Variance and continued with Duncan's Multiple Range Test